Somatic Lexemes in the Kartvelian Linguistic Space (European Journal of Language and Literature, 2019)
Comparative-historical study of languages makes it possible to represent the diachronic process of structuring the world and forming the corresponding concepts. The abovementioned process is inherently integral and reflected in such socio-cultural areas of human life as language, art, religion, farming, ethno-traditional customs, culture (in its broadest sense), etc. The proto-language reconstructed as a result of the comparative-historical study and the picture of its diachronic development provide some information about the genetic relations between the people speaking the corresponding related languages, about their original homeland and the directions of their historical migrations, about their knowledge, ideas and representations. This time we have analyzed the semantic field of the lexemes denoting the human body parts, which are reconstructed at the Proto-Kartvelian language and exist in the contemporary Kartvelian languages (Georgian, Megrelian, Laz, and Svan) and some dialects (notably, Gurian, Rachian, Xevsurian, and Kiziqian). Our goal is to reveal the semantic structure of the mentioned field, to analyze the respective concepts as well as to outline processes of the development and the establishment of corresponding tokens (resp. lexemes). Vocabulary denoting a human body (resp. Somatic lexemes), its parts and inner organs is a constituent part of the basic core vocabulary of a language and presumably ought to be fixed in the ancient times’ reflecting data. Analysis of the lexical units, which have been reconstructed either at the Common-Kartvelian or Georgian-Zan level on the basis of regular sound correspondences between the Kartvelian languages, allows us to highlight the main course of forming and developing the linguistic units we are concerned with; namely, the accumulation of “knowledge” had been carried out due to the process of differentiation and detailed elaboration of the human body anatomy and respectively, the corresponding semantic field, somatic vocabulary, had been underway to be enriched based on the relation of cognitively interpreted markedness. Language changes and development, formation of new categories and concepts, and consequently, creation of new linguistic units is mainly carried out as the result of detailed elaboration, further specification and partition of unmarked categories: an unmarked category undergoes the division-differentiation on the basis of formally marked oppositions that leads to the formation of new linguistic units and structures and reflects the dynamic picture of enhancement of linguistic cognition of the universe. Dialectic material enriches the semantic space even more and specifies and fills the meanings of lexemes to be studied.